Coenzyme Q10 supplementation in non-alcoholic fatty liver disease: an overview. (2nd April 2020) - Mantle, David; Hargreaves, Iain P
Abstract : Non-alcoholic fatty liver disease is the most common liver disorder in the UK, for which little effective conventional treatment is available. Mitochondrial dysfunction, oxidative stress and inflammation have been implicated in the pathogenesis of non-alcoholic fatty liver disease. This article focuses on the role of the vitamin-like substance coenzyme Q10 in non-alcoholic fatty liver disease, since coenzyme Q10 plays a key role in mitochondrial function, as well as having antioxidant and anti-inflammatory action. Coenzyme Q10 levels are depleted in non-alcoholic fatty liver disease, and studies in animal models and human subjects have indicated that supplementation with coenzyme Q10 can significantly reduce oxidative stress and the inflammation characteristic of non-alcoholic fatty liver disease. In addition, Non-alcoholic fatty liver disease patients are at increased risk of developing heart failure, and supplementary coenzyme Q10 may help to reduce this risk. Supplementary coenzyme Q10 is generally well tolerated, with no significant adverse effects reported in long-term use.